Underlying microangiopathy and functional outcome of simultaneous multiple intracerebral hemorrhage - Li, Jiawen; Shen, Dan; Zhou, Yanli; Jin, Yujia; Jin, Luhang; Ye, Xianghua; Tong, Lusha; Gao, Feng (Frontiers in Aging Neuroscience, 2022)
Objective To identify the predominant type of cerebral small vessel disease (SVD) and outcomes in patients with simultaneous multiple intracerebral hemorrhages (SMICH). Methods Consecutive patients with intracerebral hemorrhage (ICH) from a single-center prospective cohort were retrospectively reviewed. Presumed etiology was classified according to the SMASH-U criteria. Demographics, clinical and laboratory variables, and neuroimaging data were compared between patients with primary SMICH and those with single ICH. Functional outcomes were assessed using the modified Rankin scale 90 days after ICH. Results Of the 598 enrolled patients, 37 (6.2%) met the criteria for SMICH. Risk factors for SMICH included a high burden of deep cerebral microbleeds (CMBs) (odds ratio [OR] 1.06, 95% confidence interval [CI], 1.00–1.12; p = 0.040), white matter hyperintensity scores (OR 1.27, 95% CI 1.04–1.57; p = 0.021), history of ICH (OR 3.38, 95% CI 1.31–8.05; p = 0.008), and low serum magnesium levels (OR 0.01, 95% CI 0.00–0.25; p = 0.007). Based on the SMASH-U classification, 15(40.5%) SMICH were classified as hypertension, whereas 17 (45.9%) as undetermined-etiology. To further explore the potential microangiopathy underlying undetermined-SMICH, these patients with undetermined-etiology were compared to those with cerebral amyloid angiopathy-ICH, and were associated with a higher burden of deep CMBs but less severe centrum semiovale enlarged perivascular spaces. Likewise, compared with hypertension-ICH patients, those with undetermined SMICH were consistently associated with a higher deep CMB counts. Moreover, multivariate analysis revealed that SMICH was independently associated with poor outcomes (OR 2.23, 95%CI 1.03–4.76; p = 0.038). Conclusion Our results suggest that most patients with primary SMICH harbor hypertensive-SVD as principal angiopathy. Patients with SMICH are at a high risk of poor outcomes. (ClinicalTrials.gov Identifier: NCT 04803292).